PROSTATIC ADENOCARCINOMA IN DOG: A CASE REPORT - MENON, KIREN; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, T G; MURTHY, V C; MURTHY, NARASIMHA (The Indian Journal of Animal Reproduction, 2023)
A case of ProstaticAdenocarcinoma in a dog was reported.